Case Report: Congenital Coronary Artery Ring With Single Left Coronary Ostium and Fistula: A Previously Unreported Anatomy - Tang, Shiyuan; Tang, Mi; Daniel Iroegbu, Chukwuemeka; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Background: Single coronary ostium concomitant with coronary artery fistula is a very rare congenital anomaly. Apart from that, the combination of a closed loop of the coronary artery has never been reported. Case presentation: Herein, we present a 7-year-old girl diagnosed as single left coronary ostium with a giant coronary trunk, coronary artery to right ventricle fistula, and coronary artery ring. The coronary fistula was surgically ligated with off-pump strategy and the patient discharged on postoperative day 5 and free of symptoms during the 3 years of follow-up. Conclusion: To our knowledge, the presented congenital coronary anomaly is the first to be reported in the literature with the name of congenital coronary artery ring with single left coronary ostium and fistula.